Management of Teachers and Supervisors of Religion in Government Schools in Indonesia : Policy Note - Hartono, Djoko; Trang, Eddy Quach (World Bank, Washington, DC, 2020)
In Indonesia, religious education in schools is part of the national curriculum and is intended to promote greater understanding of one’s religion, in addition to tolerance and mutual respect between adherents of religion in personal, community and state life. However, key knowledge gaps exist regarding the current state of delivery of religious education, limiting efforts to develop reforms for improvement. To help in addressing this knowledge gap and at the request of the Ministry of Religion (MoRA), the World Bank analyzed the current state of management of teachers (GPAs) and supervisors (PPAs) of religion. To undertake this analysis, the team collected extensive qualitative and quantitative data between August 2018 and April 2019. Overall findings from the study reveal several management‐related issues that likely limit effective delivery of religious education in Indonesia. Part 1 of this note analyzes management issues of GPAs, while part 2 focuses on PPAs.